Teaching from the emerging now - Werner, Linnette Robin; Hellstrom, David (Emerald Publishing Limited, 2021)
Microaggressions, complex identities, polarized belief systems, pandemic interruptions-these are just a few of the things the modern classroom holds. What if we could work with what 'emerges' in the moment instead of seeing it as an unplanned disruption? 'Teaching from the Emerging Now' explores how we combine our intention with what naturally emerges to create inclusive, dynamic classrooms amid constant change. The Intentional Emergence model combines Case-in-Point and Adaptive Leadership with compassion and culturally responsive pedagogy to develop a new teaching and learning style. This approach takes the fear out of being surprised, provides concrete ways to both support and challenge students, and reimagines the classroom as a living leadership laboratory. Beyond bridging theory to practice, by rethinking the classroom from a place to impart knowledge to a shared space of co-creation, faculty, teachers, and trainers are better able to meet the increasingly diverse needs of learners.
Includes index.
Keywords: Classroom environment.; Classroom management.; Teaching.; Education -- Classroom Management.; Educational strategies & policy.; elektronické knihy; electronic books